2002
DOI: 10.1515/jpem.2002.15.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Development in the Children of Mothers with Type 1 Diabetes Mellitus or Gestational Diabetes Mellitus

Abstract: The purpose of this study was to examine psychomotor development in children born to mothers with type 1 diabetes mellitus (DM1) or gestational diabetes mellitus (GDM). The influence of metabolic control in pregnant diabetic mothers and complications during labor on their children's psychological and physical development was evaluated. The analysis included 59 children, 20 of mothers with GDM, 19 of mothers with DM1, and 20 children of healthy mothers. Clinical observations and medical history were recorded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…One study suggested that the rate of perinatal mortality in women with type 2 DM might be higher than that of women with type 1 [3]. It is well documented that children of mothers with insufficiently treated DM have a much higher risk of developing juvenile DM, obesity and hypertension and have reduced psychomotor and intellectual development [4][5][6]. It is therefore essential to achieve good metabolic control from before conception to the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…One study suggested that the rate of perinatal mortality in women with type 2 DM might be higher than that of women with type 1 [3]. It is well documented that children of mothers with insufficiently treated DM have a much higher risk of developing juvenile DM, obesity and hypertension and have reduced psychomotor and intellectual development [4][5][6]. It is therefore essential to achieve good metabolic control from before conception to the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…However, all of these studies were performed in healthy, nondiabetic mothers and their children. ODM have delayed neuropsychological and cognitive development (7)(8)(9)(10). Most interestingly, delayed speech development in ODM has been described (10).…”
Section: Discussionmentioning
confidence: 99%
“…Offspring of diabetic mothers (ODM) have delayed psychomotor and cognitive development (7)(8)(9)(10). Pathophysiologic mechanisms remain unknown.…”
mentioning
confidence: 99%
“…226 Rapid eye movements, a surrogate of brain maturation, were also found to be reduced in offspring of diabetic mothers. 237,238 Additional studies have demonstrated a high rate of inattention, hyperactivity and fine and gross motor impairment in OT1DM. 229,230 In contrast, some more recent series have not found similar IQ impairment 231,233 or relationships to acetonuria.…”
Section: Neurological Developmentmentioning
confidence: 99%